1989
DOI: 10.1055/s-2007-1025302
|View full text |Cite
|
Sign up to set email alerts
|

Zur Problematik der chronischen Claviculaosteomyelitis

Abstract: From 1978 to 1987, 139 children were treated for osteomyelitis at our institution, among them 6 with osteomyelitis of the clavicle. All six patients presented with a primary chronic osteomyelitis. Three children sustained a trauma anamnestically. Pathohistological examinations revealed a chronic, unspecific inflammation in all cases. Immobilisation was achieved by means of a DESAULT-cast or an abduction splint for 7 to 36 weeks, antibiotics (clindamycin) were given for 6 to 55 weeks, starting with intravenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In a series of 38 children with osteomyelitis Mah et al reported 2.6% incidence of clavicular involvement [ 6 ]. In a case series of 139 children, Dietz et al reported 4.31% incidence of chronic clavicular osteomyelitis [ 7 ]. MRSA is an established nosocomial infection and most common pathogen reported for this rare entity.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of 38 children with osteomyelitis Mah et al reported 2.6% incidence of clavicular involvement [ 6 ]. In a case series of 139 children, Dietz et al reported 4.31% incidence of chronic clavicular osteomyelitis [ 7 ]. MRSA is an established nosocomial infection and most common pathogen reported for this rare entity.…”
Section: Discussionmentioning
confidence: 99%